2020
DOI: 10.2196/24693
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Using COVID-19 mHealth Tools Among Adults With Chronic Health Conditions: Secondary Data Analysis of the COVID-19 Impact Survey

Abstract: Background Adults with chronic conditions are disproportionately burdened by COVID-19 morbidity and mortality. Although COVID-19 mobile health (mHealth) apps have emerged, research on attitudes toward using COVID-19 mHealth tools among those with chronic conditions is scarce. Objective This study aimed to examine attitudes toward COVID-19, identify determinants of COVID-19 mHealth tool use across demographic and health-related characteristics, and evalu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 100 publications
(68 reference statements)
1
31
0
Order By: Relevance
“…Since the onset of the COVID-19 pandemic, similar surveys have been conducted worldwide to better understand people's attitudes on the use of COVID-19 related apps [14] , [27] , [39] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] . In many of these studies, the impact of gender, social, and demographic factors in different communities have been reported with different results, as presented in Table 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the onset of the COVID-19 pandemic, similar surveys have been conducted worldwide to better understand people's attitudes on the use of COVID-19 related apps [14] , [27] , [39] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] . In many of these studies, the impact of gender, social, and demographic factors in different communities have been reported with different results, as presented in Table 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, patients with chronic health conditions such as cardiometabolic diseases, respiratory conditions, immune-related conditions, mental health, and obesity are more likely to use COVID-19 mHealth applications. 27 Researchers in China have also identified that parents' willingness to adopt mHealth for their children during the pandemic was relatively high. 28 Considering the benefits of mHealth applications investigated in developed countries during the current situation, the authors are motivated to discover mHealth adoption among developing countries.…”
Section: The Roles Of Mhealth In Mitigating the Covid-19 Pandemic In The Developing Countriesmentioning
confidence: 99%
“…Moreover, 24% of the participants were likely to use TH apps to avoid infected locations. Overall, people with severe chronic lung diseases used TH apps more often than those without chronic lung diseases (OR and 95% CI: 1.23, 1.04 to 1.45) [68]. A recent study reported that clinicians were able to evaluate symptom severity (95%), promote smoking cessation (84%) and signpost to other healthcare resources (80%) [69].…”
Section: Telehealth Applicationsmentioning
confidence: 99%